Defining Entrepreneur’s Business Reputation In Research By The Russian Civil Lawyers - Dmitrieva, Olga V. (Opción, 2019)
The research is aimed at defining the nature of the entrepreneur’s business reputation as an object of civil rights. Major research methods include general scientific special juridical methods. The article proves that the entrepreneur’s business reputation does not acquire the features of property, but preserves the most basic attributes of an intangible benefit, namely, it is inherent in an individual and cannot be estimated in monetary form. Thus it cannot be an independent subject of a civil-law contract. As an intangible benefit, business reputation has an economic (property) function in the property relations.